Analysis of the Content Validity of the Elementary Teacher Belief Instrument on TPACK and Its Use in Distance Learning - Aprilia, Tika; Mustadi, Ali; Ardiansyah, Amalia Rizki (Universitas Veteran Bangun Nusantara, 2023)
Teachers are required to have adequate technological, pedagogical, and content knowledge (TPACK) in supporting distance learning. The purpose of this study is to prove validity of instrument content 1) to identify the elementary school teachers’ towards the use of TPACK, and 2) the use of TPACK in distance learning. The two instruments in this study were developed into 7 indicators. This research method is a descriptive research method using quantitative descriptive analysis techniques. Where the results of proving the validity of the contents were carried out by experts and analyzed using Aiken's V formula with a minimum standard of V Aiken is ? 0.88. The results showed that the coefficient of validity of the contents of 30 aitems in the teacher's belief instrument against TPACK there were 28 aitems that were declared valid with a value of ? 0.82, while the instrument of use of TPACK in distance learning obtained for the coefficient of validity of the contents of 30 aitems there were 24 aitems that were declared valid with a ? value of 0.76. Therefore, this instrument can be used to identify the elementary school teachers’ belief in Indonesia and Malaysia towards TPACK and its use in distance learning